The Influence of Students’ Engagement on Learning Comprehension of Maritime Insurance Course - Langandriansyah Dwi Yatno (CV. Creative Tugu Pena, 2025)
This study examines the influence of students’ engagement on learning comprehension in the Maritime Insurance course at Politeknik Pelayaran Sumatera Barat. Motivated by concerns about vocational learning effectiveness and graduates’ professional readiness, the study’s primary objective was to test whether students’ engagement affects learning comprehension and to quantify the magnitude of this effect. A quantitative, comparative design was employed using an independent-samples t-test to compare two groups defined by engagement level. The population comprised 153 students enrolled in the Marine Transportation program for the 2025/2026 academic year; samples were selected via quota-based random sampling, yielding two groups of 103 respondents each. The t-test results showed t-calculated = 24.578 versus t-critical = 1.66 with p < 0.05, leading to acceptance of the hypothesis that students’ engagement significantly influences learning comprehension. Effect-size analysis produced Cohen’s d = 3.43, indicating a very large practical effect and substantial mean differences between groups with differing engagement levels. These findings underscore the importance of active learning strategies and interventions that enhance behavioral, emotional, and cognitive engagement to strengthen conceptual mastery and workplace readiness in maritime contexts; practical implications include integrating claims simulations, authentic tasks, and targeted formative feedback. The study recommends future research employing objective outcome measures and longitudinal or experimental designs to improve generalizability and clarify causal mechanisms.